Proteomic analysis of secretory proteins and vesicles in vascular research - Pula, Giordano; Perera, Sue; Prokopi, Marianna; Sidibe, Anissa; Boulanger, Chantal M; Mayr, Manuel (My University, 2008)
The release of proteins and membrane vesicles in the bloodstream regulates diverse vascular processes, both physiological, such as angiogenesis and haemostasis, and pathological, such as atherosclerosis and atherothrombosis. Proteomics, beside its canonical application for the expression profiling in cells and organs, can be applied to the study of secreted proteins and microvesicles, which play a significant role in the homeostasis of the vasculature, and the development of the atherosclerotic disease.
Keywords: Atherosclerosis; Cardiovascular; Microparticles; Secretory proteins